'Where's the money coming from?' Manifesto costings and the politics of fiscal credibility in UK general elections, 1955–2019. (August 2021) - Sloman, Peter
Tax and spending are central to democratic politics in the United Kingdom and elsewhere, but psephologists have paid surprisingly little attention to the practice of manifesto costings or the ways in which fiscal promises shape voting behaviour. This article uses qualitative research to trace how British parties have used manifesto costings to frame prospective choices for voters since the 1950s and develops a theoretical framework for understanding why warnings about 'tax bombshells' and 'black holes' in parties' spending plans seem to be so powerful in Britain. The article suggests that the emphasis which governments have placed on budgetary constraints since the 1976 International Monetary Fund (IMF) crisis may help explain the long electoral cycles the United Kingdom has experienced in recent decades. Whereas retrospective economic evaluations can be difficult for governments to control, forward-looking fiscal debates are structurally weighed towards incumbent parties and offer a powerful way for incumbents to offset the 'costs of governing'.